LAPORAN KASUS : PENANGANAN OBSTRUKSI USUS PADA ANJING DI BALI VETERINARY CLINIC - Ludji Pau, Putri F.; Simarmata, Yohanes T. R. M. R.; Restiati, Ni Made (JURNAL KAJIAN VETERINER, 2021)
A local breed dog was brought to the veterinary clinic with signs of vomiting and decreased appetite. Physical examination revealed a pale mucosa of the eye and nose, 2 seconds of CRT, abdomen distention and stiffness. A haematology examination indicated WBC drop into 4.9, lymphocyte into 5.4, MCV to into 55.42 and Plate Distribusi Wide 8.1. The X-ray test showed the presence of an unknown mass around the intestine. Therefore, the dog was then diagnosed with intestinal obstruction. A laparotomy exploration with an enterotomy technique was performed to treat the condition. The surgery procedure found a mass of stone-like faeces that also consist of a mix of grass. The stone-like faeces were then removed from the intestine. Post-surgery monitoring was performed routinely and the dog received Cefotaxime Sodium (Claforan®) 22 mg/kg, Odansentron HCl (Zofran®) 0.2 mg/kg, Sucralfate (Carafate®) 0.8 gram, Lactulose (Cephulac®) 25 mL, Dexamethasone (Dexasone®) 1 mg/kg, Diphenhydramine HCl (Benadryl®) 3mg/kg, along with antiseptic treatment for the surgical incision. 3 days after the operation the dog began to show signs of recovery where the dog appeared to start moving and showed the desire to eat food. This condition can be prevented by not giving the dog food that bones. Lastly, the dog should be only released in a safe and knowledgeable environment.